Implementasi green marketing pada FiPuA - Angela, Ni Made Utari Tisna; Wajdi, Majid; Sanjaya, Ida Bagus; Arbainah, Siti (Journal of Commerce, Management, and Tourism Studies, 2022)
The tourism industry sector is in second place as Indonesia's biggest foreign exchange contributor but on the other hand, Indonesian tourism is still considered to be a world that is not environmentally friendly, so it becomes a new challenge for tourism industry players to solve these problems together. Hospitality is a part of the tourism service industry which has a fairly rapid development and plays an important role in tourism in a region and is supposed to implement green marketing in running its business. This study aims to analyze and determine the implementation of green marketing strategies and the efforts of the company. This research was conducted directly in one of the tourism service industries that provides accommodation services and has implemented a green marketing strategy in running its business to be used as a place of research. Observation and document study was done to provide the data of the research. Based on the results of the study, the quality of the green marketing strategy of the company is "A" namely "Special" with a final score of 86.78. The dominant strategy carried out by companies is to preserve the surrounding environment with the highest average value of 4.72. In implementing a green marketing strategy, the efforts made by the company are by referring to the Tri Hita Karana implementation guidebook which in principle maintains a balanced life and harmonious relationship with God, and fellow humans and helps preserve the environment around.